Fe-pyridinedicarboxylate based coordination polymer nanorods as a heterogeneous Fenton catalyst for pollutant degradation - Li, Wen-Juan; Liu, Huan; Guo, An; Chang, Lan; Yao, Xi-Yuan; Sun, Bi-Zhu; Meng, Jia-Lin; Li, Yue; Ruan, Wen-Juan (RSC advances, 2016)
A Fe-pyridinedicaroxylate based coordination polymer with a monodisperse morphology of nanorods was synthesized under solvothermal conditions. This compound could work as a heterogeneous Fenton catalyst to degrade a series of organic pollutants, and exhibited high activity, good stability, a wide pH tolerance and efficient H 2 O 2 utilization in the reactions. A Fe-pyridinedicaroxylate based nanoscale coordination polymer works as a Fenton catalyst to degrade pollutants by the formation of &z.rad;OH and high-valent iron species.